PENGEMBANGAN MEDIA PEMBELAJARAN PERANGKAT KERAS JARINGAN BERBASIS AUGMENTED REALITY PADA PLATFORM ANDROID - Saidina Hamzah; Denny Kurniadi (Universitas Negeri Padang, 2019)
The limitedness number of teaching media such as projector and networking hardware in SMK N 2 of padang causes the learning activities especially WAN (Wide Area Network) Technology to be not optimal. Therefore, the material learning activities become one-way and unattractive. The school prohibit students to borrow networking hardware, so that the process of recognizing the physical form of network devices occurs only during laboratory activities. These learning causes inefficient use of study time. Students often abuse the use of smartphones in school as entertainment media. ARSchool networking Hardware Learning Media was developed to overcome this problem. The Marker Based Tracking Method of Augmented Reality technology was utilized to display three-dimensional objects (3D) on an Android Smartphone. The 3D objects of network devices was designed by using the Blender application. The making of media was based on WAN Technology syllabus used by school. The design of media used Unity and Vuforia application as database of image target or marker. With this learning, students could easily learn the networking hardware of WAN Technology anywhere and anytime. The feasibility test shows that this learning media is very practical (95,45%) and very valid (94,47%). This media is equipped with the explanation of parts of the devices that is displayed in the form of text, image and audioKeywords: Learning Media, Augmented Reality, Android, Network Hardware.